KAJIAN VARIABEL-VARIABEL YANG MEMPENGARUHI HASIL TANGKAP IKAN DAN KELAYAKAN INVESTASI KAPAL PENANGKAP IKAN DI INDONESIA - Sri Waluyo, Bambang (Department of Naval Architecture - Diponegoro University, 2006)
Bambang Sri Waluyo in paper variable about fishing cacch and feasibility study investation for Catching Vessel. The success of fishing cacch depending of many variable among, Tecknology and equipment of Caching,Dimention of Ship, Fishing Ground. The capital of investment depent scale of firm Prospectus of benefit, term of pay back period (PP),Marginal Efisiency of Capital(MEC), Profit Rate (PR), Break Event Point (BEP), and Benefit Cost Ratio (B/C).